Peran Guru Pendidikan Jasmani dalam Membentuk Karakter Peserta Didik di SMAN 1 Cilamaya - Sekar Harum Wulandari; Febi Kurniawan; Rolly Afrinaldi (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research is motivated by social phenomena in the educational environment which closely related to the reduction of student character. The efforts to improve character education have been carried out by the government through Character Education Strengthening Programs. The purpose of this study is to describe how the practice of the Character Education Strengthening Program such as heart, thought, exercise, taste and intention is carried out in schools, especially in SMAN 1 Cilamaya. This research uses a mixed approach with descriptive analysis method. The theory used in this research is the Government of the Republic of Indonesia regarding the National Policy for National Character Development in 2010-2025. The results showed that character education has been applied and applied to students in the physical education learning process such as spiritual character, honesty, trustworthiness, fairness, orderly rules, responsibility, empathy.